Scenario development for the observation of alpha-driven instabilities in JET DT plasmas. (29th June 2018) - Dumont, R. J.; Mailloux, J.; Aslanyan, V.; Baruzzo, M.; Challis, C.D.; Coffey, I.; Czarnecka, A.; Delabie, E.; Eriksson, J.; Faustin, J.; Ferreira, J.; Fitzgerald, M.; et al.
Abstract: In DT plasmas, toroidal Alfvén eigenmodes (TAEs) can be made unstable by the alpha particles resulting from fusion reactions, and may induce a significant redistribution of fast ions. Recent experiments have been conducted in JET deuterium plasmas in order to prepare scenarios aimed at observing alpha-driven TAEs in a future JET DT campaign. Discharges at low density, large core temperatures associated with the presence of internal transport barriers and characterised by good energetic ion confinement have been performed. ICRH has been used in the hydrogen minority heating regime to probe the TAE stability. The consequent presence of MeV ions has resulted in the observation of TAEs in many instances. The impact of several key parameters on TAE stability could therefore be studied experimentally. Modeling taking into account NBI and ICRH fast ions shows good agreement with the measured neutron rates, and has allowed predictions for DT plasmas to be performed.